Investigation of Escherichia coli O157 and some virulence genes in samples of meat and faeces from clinically healthy cattle in Turkey - Ongor, H.; Kalin, R.; Cetinkaya, B. (British Veterinary Assoc, 2007)
[Abstract Not Available]
Keywords: Multiplex Pcr Assays; Bovine Carcasses; Turkish Cattle; Fecal Carriage; Contamination; Prevalence; Slaughter; Beef; Identification; Infections